1996
DOI: 10.1159/000244370
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental Study of Rat Renal Prostaglandin Synthesis during Development

Abstract: The biosynthesis of prostaglandins (PGs) from the endogenous and exogenous precursor, arachidonic acid (AA), in renal papilla, medulla and cortex from neonatal to adult rats was investigated. Rat renal papilla and medulla incubated in the presence of [1-14C]AA released radioactive PGE2, PGF and PGD2 which increased with age. No radioactive prostaglandins were found in the supernatants of renal cortex at any age studied. The amount of total prostaglandins released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…1C). This profile is similar to the prostaglandin profile of the renal medulla [23]. PGs synthesis varied following the kinetic of COX-2 protein expression.…”
Section: Resultssupporting
confidence: 61%
“…1C). This profile is similar to the prostaglandin profile of the renal medulla [23]. PGs synthesis varied following the kinetic of COX-2 protein expression.…”
Section: Resultssupporting
confidence: 61%
“…The aim of the present report was to find an enzymatic basis that could explain the changes in arachidonate homeostasis and metabolism that occur during kidney maturation [2,4,13]. We had previously demonstrated that in newborn rats renal membrane phospholipids are almost depleted of arachidonic acid [4], show high avidity for exogenous arachidonic acid [2], and low prostaglandin synthesis [13]; while kidney maturation seemed to be characterized by enrichment in membrane arachidonic acid [4] and increase in prostaglandin synthesis [13].…”
Section: Discussionmentioning
confidence: 90%
“…As we have previously shown, in the neonatal kidney arachidonate content is low, fatty acid availability is scarce and cyclooxygenase activity is also low [4,13]. Thus, a highaffinity acyl-CoA synthetase is necessary to accomplish the storage of arachidonate in membrane phospholipids in the presence of a demand for prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For the neonatal kidney little is known about the synthesis of the different prostaglandins and the expression of their specific receptors. A recent paper describes a low COX activity and consequently a low release of prostaglandin E 2 (PGE 2 ) in the cortex of the newborn rat, whereas the medulla was a rich source of PGE 2 , PGF 2á and PGD 2 [22]. However, the expression of specific PGE 2 receptors was shown in the neonatal rat cortex [23].…”
Section: Introductionmentioning
confidence: 99%